Photometric and spectroscopic variability of the Be star 48 Lib: The relation between photometric variations and rotation. (23rd November 2018) - Ozuyar, D.; Caliskan, S.; Stevens, I. R.; Elmasli, A.
Abstract: The purpose of this paper is to determine the origin of the photometric variations of 48 Lib using the data from the STEREO and to investigate their relations with the disk structure. The photometric data comprise a period of five years from 2007 to 2011. The spectroscopic data covering the same time interval are provided from the BeSS database. The H α lines are examined by measuring their equivalent widths and line intensities. H α variations are then compared with those displayed by the photometric data. From the photometry, high-precision results (10 −5 c d −1 in frequency and 10 −4 mag in amplitude) are obtained. It is detected that the star has shown 24 frequencies, mainly clustered around the peaks at 2.48896(1) and 5.08150(2) c d −1 . The analysis reveals that the photometric frequencies are not due to pulsation, but caused by the rotation, and that the remaining frequencies arise from transient activities on or just above the photosphere. Also, it is shown that the spectroscopic data exhibit a significant H α variability, and that the H α line variation depends on the variation of frequency and amplitude, something which has been often proposed in the literature but has never before been demonstrated observationally. This proves that the disk structure and photometric variations are related.